UPAYA BADAN PENGAWAS PEMILIHAN UMUM DALAM PENANGGULANGAN TINDAK PIDANA MONEY POLITIC - Samaluddin, Samaluddin; Wiridin, Darmawan; Karim, Saiful (Jurnal Ilmu Hukum Kanturuna Wolio, 2025)
This research aims to understand the efforts of the Election Supervisory Agency (Bawaslu) in preventing money politics, especially in Tarafu Village, Batupoaro Subdistrict, Baubau City, and the inhibiting factors faced by the Election Supervisory Agency in eradicating money politics in Tarafu Village, Batupoaro Subdistrict, Baubau City. The research method employed is literature review and field study with the principles approach using Law Number 7 of 2017 and the Constitution of the Republic of Indonesia. The research specification is descriptive. Data sources involve direct question and answer sessions with election organizers including the General Election Commission (KPU), the Election Supervisory Agency (Bawaslu), involved legislative candidates, and the residents of Tarafu Village, Batupoaro Subdistrict, Baubau City, as well as books and internet articles related to the researched title. The data collection method is literature review. The data presentation method is in the form of narrative text, systematically outlined. Data analysis is qualitative. Based on the results of the research and discussion in this thesis, it can be concluded that the efforts of the Election Supervisory Agency in preventing money politics, especially in Tarafu Village, Batupoaro Subdistrict, Baubau City, are through intensive socialization, direct enforcement against violations, and internal capacity building. Although there are reports from the Subdistrict Election Supervisory Committee (Panwascam), most do not meet the material criteria for further action. Overall, these efforts by Bawaslu have succeeded in reducing the practice of money politics, although there are still challenges in collecting evidence and handling reports. The inhibiting factors faced by the Election Supervisory Agency in combating Money Politics in Tarafu Village, Batupoaro Subdistrict, Baubau City are as follows: Economic Factors, Cultural Factors, and Lack of Public Knowledge About Politics.